Mass of the postsynaptic density and enumeration of three key molecules - Chen, Xiaobing (National Academy of Sciences, 2005)
The total molecular mass of individual postsynaptic densities (PSDs) isolated from rat forebrain was measured by scanning transmission EM. PSDs had a mean diameter of 360 nm and molecular mass of 1.10 ± 0.36 GDa. Because the mass represents the sum of the molecular masses of all of the molecules comprising a PSD, it becomes possible to derive the number of copies of each protein, once its relative mass contribution is known. Mass contributions of PSD-95, synapse-associated protein (SAP)97, and α-Ca(2+)/calmodulin-dependent protein kinase II (CaMKII) were determined by quantitative gel electrophoresis of PSD fractions. The number of PSD-95 molecules per average PSD, contributing 2.3% of the mass of the PSD, was calculated to be 300, whereas the number of SAP97 molecules, contributing 0.9% of the mass of the PSD, was 90. The α-CaMKII holoenzymes, which contribute 6% of the mass when brains are homogenized within 2 min of interrupting blood flow, have 80 holoenzymes associated with a typical PSD. When blood flow is interrupted 15 min before homogenization, the average mass of PSDs increases by ≈40%. The additional α-CaMKII associated with PSDs accounts for up to 20% of this mass increase, representing the addition of 100–200 α-CaMKII holoenzymes.